Application of Chili (Capsium annulum Sp.) as Cotton Wood (Hibiscus tiliaceus L.) Preservatives with Vacuum Soaking Methods - Susilo, Bambang; Argo, Bambang Dwi; Mubarok, Luthfi (Fakultas Teknologi Pertanian Universitas Brawijaya, 2011)
Chili (Capsium annulum Sp.) is used as preservatives of Cotton Wood (Hibiscus tiliaceus L.) with vacuum pressure soaking method with full cellar process. The objectives of this study were to reveal the comparison between preserved and un-preserved wood based on its compressive strength and flexural strength, to investigate the effect of various concentrations of preservatives (i.e. 10, 20, and 30%) on biological and a mechanical wood properties, and to know the resistency of cotton wood (Hibiscus tiliaceus L.) to decrease quality caused by insect wood destroying or other organic materials. Preservation method used in this study was vacuum pressure soaking method with full cellar process and the preservative was the chili (Capsium annulum Sp.) solution. The research was conducted with Completely Randomized Design with treatment of various concentrations of chili solution (i.e. 0%, 10%, 20% and 30%) with five repetitions. The data were analyzed with Anova and presented by graphs. The results indicated significant differences between preserved and un-preserved cotton wood, both on mechanical testing and organic damage. After 24 days of observation, damage caused by insect was found in un-preserved wood, but none could be identified in those which were preserved. Keywords : preservation, cotton wood, chili, vacuum pressure soaking